Implementation of Primary School Teacher Certification Policy - Judijanto, Loso; Susanti, Melly (PT FORMOSA CENDEKIA GLOBAL, 2024)
A teaching certificate serves as proof of recognition of a teacher's status as a professional. This study aims to determine the implementation model of the primary school teacher certification policy in Seluma Regency, Bengkulu Province. This qualitative research method collects data through a qualitative approach and descriptive approach to explain and describe the implementation of the teacher certification policy. The results obtained show that the lack of socialization facilities and infrastructure, coupled with the absence of socialization of teacher certification since 2012 until now, has made the primary school teacher certification policy in Sukaraja Sub-district, Seluma Regency, difficult to implement. Relevant parties from the Seluma District Education Office have not been able to offer the most effective solutions to the problems faced by teachers, especially in responding to regulations that are almost never consistent in the implementation of teacher certification.